THE ROLE OF GROWTH MINDSET AND SELF-COMPASSION ON SUBJECTIVE WELL-BEING IN ADOLESCENTS - Reza, Muhammad; Finnalia, Shania; Wahidah, Fatin (Jurnal Ilmiah Penelitian Psikologi, 2023)
Adolescents as individuals who are in the transitional period of development from childhood to adulthood. A person with a high level of subjective well-being has the ability to regulate emotions and cope well with problems. Self-compassion reflects a good attitude towards oneself, by not blaming the conditions, shortcomings, and experiences that occur in adolescents. The development of an individual’s mindset can make an individual’s life more advanced or even vice versa can be more or less good. This study aims to determine the effect of growth mindset and self-compassion on the subjective well-being of adolescents. The research method used in this study is a quantitative approach. Samples in this study were early adolescents aged 13-17 years in adolescents in Purbalingga. This study uses non-random sampling techniques, sampling used is quota sampling. Data collection was carried out using questionnaires with three measuring instruments, namely the subjective well-being scale from Diener (2009), the self-compassion scale from Neff (2003), and the growth mindset scale from Chen (2021) which has reliability coefficients of 0.785; 0.747; 0.727. The results showed that the growth mindset effect on subjective well-being by (17.0%) and self-compassion effect on subjective well-being by (42.5%). Together, growth mindset and self-compassion affect subjective well-being by 32.0%. So with this it can be concluded that H1 is accepted, H2 is accepted and H3 is accepted. If the number or direction of the regression coefficient is positive ( + ) then the direction of the line increases (increases) while if it is negative ( - ) then the direction of the line decreases (decreases). In this study the positive regression value can be stated that growth mindset and self-compassion have a positive effect on subjective well-being in adolescents. The results and discussion of the study will be discussed further in the article.